The Integrated Knowledge Centre: A Partnership Between UK Higher Education and Engineering Industry - Sansom, Christopher L.; Shore, Paul (Common Ground Publishing, 2012)
We discuss the creation of an Integrated Knowledge Centre, a unique collaboration between academia and industry, which is delivering to UK industry 'disruptive' technologies based on ultra precision engineering. The partners include Cranfield University, the University of Cambridge, University College London, and the OpTIC Technium. This paper concentrates on the development of Knowledge Transfer systems and the successful implementation of processes for the delivery of postgraduate taught courses, short courses for industry, and distance learning packages. In order to retain competitive advantage, UK precision engineering industry requires a regular supply of technically proficient and organizationally prepared graduates. This paper explains the approach taken by Cranfield University and its partners to increase the size of the pool of postgraduate precision engineers and to enhance the skills of industrially based engineers. The approach involves the design of a multi-level system, which draws on increased connectivity between the University, UK Engineering companies, and the student. The main vehicle for providing the technical training is the postgraduate Masters degree in "Ultra Precision Technologies". We explain how this course has been designed for broad appeal, whilst incorporating world class technical teaching and an external focus on the needs of participating companies.
Keywords: Knowledge Transfer, Engineering, Postgraduate, UK Higher Education